Precipitation in and Supersaturation of Contents of the Upper Small Intestine After Administration of Two Weak Bases to Fasted Adults - Psachoulias, Dimitrios; Vertzoni, Maria; Goumas, Konstantinos; Kalioras, Vasilios; Beato, Stefania; Butler, James; Reppas, Christos (Pharmaceutical research, 2011)
ABSTRACT Purpose To evaluate precipitation in and supersaturation of intestinal contents after administration of pharmacologically relevant doses of dipyridamole and ketoconazole to 12 healthy adults. Methods On two separate days each subject was administered in stomach 240 ml aqueous solutions of two dipyridamole doses (30/90 mg) and two ketoconazole doses (100/300 mg). Physicochemical characteristics, total drug content, and drug concentration were measured in individual intestinal contents (≤7 ml) aspirated at specific times post-dosing. Drug concentration after incubation (37°C/48 h) and equilibrium solubility were measured. Precipitate crystallinity was evaluated by x-ray powder diffraction. Results Precipitated fraction was minimal (dipyridamole, ≤7%) or limited (ketoconazole, ≤16%). Ketoconazole precipitates were mostly amorphous. Depending on dose, intestinal contents with pH > 3.6 were supersaturated with dipyridamole up to 10 and 30 min and with ketoconazole up to 30 and 50 min post-administration. Intestinal contents with pH > 5 and concentration of micellar components <5 mM were supersaturated with ketoconazole or dipyridamole, but precipitated fraction was significant only for ketoconazole. After incubation, crystalline precipitates were found in almost all samples. Slow precipitation of base and/or precipitation of other phases account for this observation. Conclusions Intralumenal precipitation of weakly alkaline, lipophilic, high permeability drugs may not be substantial. Estimating intestinal supersaturation in regard to free base is inadequate as other phases may precipitate.